Functional structure in nominals : nominalization and ergativity - Alexiadou, Artemis (Linguistik aktuell ;, 2001)
This monograph offers an in depth investigation of nominalization processes across languages e.g. Greek, Germanic, Romance, Hebrew, Slavic. Adopting and extending the view that category formation does not involve any lexical operation (recently put forth within the framework of Distributed Morphology), it shows how the behavior of nominals as opposed to that of verbs follows from general processes operating in specific syntactic structures, and is linked with the presence or absence of functional layers (T, D, Aspect, v). It further defines criteria on the basis of which the organization of no.